The Authority Concerning the Collection of Groundwater Taxes After the Law No. 23 Year 2014 in the City of Surabaya - Hendra Akbar Nugraha; Fikri Adiyasa Rosidin; Wimba Roofi Hutama; Muhammad Gaidy Wiratama (Yuridika, 2020)
Groundwater tax is a tax on the extraction and/or utilization of ground water. Based on Act No. 28 of 2009 concerning Local Taxes and Levies, Groundwater Taxes, the authority to collect taxes is carried out by the Municipality Government. Tax collection cannot be levied, what is meant by not being able to be bought is that the entire process of tax collection activities cannot be submitted to third parties. This provision shows that the groundwater tax collection system is a self-assessment system. The purpose of self-assessment is that taxpayers are given full trust to calculate, calculate, pay and self-report taxes owed. With this implementation, the Regional Revenue Service officers who become tax authorities are only tasked with overseeing the implementation of tax obligations by taxpayers. Tax collection cannot be levied, the authority to collect groundwater tax is given to the Provincial Government as stipulated in Act No. 23 of 2014 concerning Regional Government.